Sex Dependence of Cognitive Functions in Bipolar Disorder. (29th January 2014) - Suwalska, Aleksandra; Łojko, Dorota
Abstract : The objective of the present study was to assess the performance of lithium treated euthymic bipolar patients in tests measuring spatial working memory (SWM), planning, and verbal fluency and to delineate the influence of gender on cognitive functioning. Fifty-nine euthymic bipolar patients, treated with lithium carbonate for at least 5 yr, were studied. Patients and controls underwent a neuropsychological assessment. Bipolar patients had significantly worse results than the healthy controls in the spatial memory and planning as well as verbal fluency tests. We detected a gender-related imbalance in the SWM results. Deficits in SWM were observed in male-only comparisons but not in female-only comparisons. The SWM scores were significantly poorer in male patients than in male controls. In female-only comparisons, female patients did not have significantly poorer SWM results in any category than their controls. Bipolar women scored worse in some other tests. The present study points to the different patterns of neuropsychological disturbances in female and male patients and suggests that sex-dependent differences should be taken into account in order to tailor the therapeutic intervention aimed at the improvement of cognitive functions.